1995
DOI: 10.1136/ard.54.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Benign cutaneous polyarteritis nodosa in children below 10 years of age--a clinical experience.

Abstract: Objective-To report 10 children younger than 10 years of age with benign cutaneous polyarteritis nodosa (BCPAN). Methods-Ten children aged 1 25-10 years (mean 4-7 years; M:F = 7:3) were admitted with an unusual vasculitis. The clinical features, laboratory investigations, treatment and follow up data were analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 10 publications
0
42
0
14
Order By: Relevance
“…Malaria produces an atypical ANCA pattern and vasculitis is uncommon with this disease. Clinical presentation of malaria is very well known in endemic areas and the high amount of immune complex generated in this infection could conceivably produce cryo globulinaemic vasculitis and together with ANCA positivity may mislead the clinician (Gopinathan and Bhalla 1987;Kumar et al 1995). This is particularly so if only the immunofluorescence test is available for ANCA detection as this test has a large subjective component and atypical ANCA (X-ANCA) may be reported as just ANCA positive.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Malaria produces an atypical ANCA pattern and vasculitis is uncommon with this disease. Clinical presentation of malaria is very well known in endemic areas and the high amount of immune complex generated in this infection could conceivably produce cryo globulinaemic vasculitis and together with ANCA positivity may mislead the clinician (Gopinathan and Bhalla 1987;Kumar et al 1995). This is particularly so if only the immunofluorescence test is available for ANCA detection as this test has a large subjective component and atypical ANCA (X-ANCA) may be reported as just ANCA positive.…”
Section: Discussionmentioning
confidence: 97%
“…Malaria is usually not associated with a vasculitic illness but cryoglobulinaemia is known to be associated with malaria and can cause vasculitis (Gopinathan and Bhalla 1987;Kumar et al 1995). As these infections far outnumber the idiopathic vasculitides described above there is every possibility of misinterpreting an ANCA positivity with TB, leprosy or malaria associated erythema nodosum as paucicellular vasculitis like Wegener's granulomatosis if the classical clinical features of the infections are not present and vice versa, even in a developed country where these infections are not common but may be imported or could even be rarely indigenous.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Less common presentations include inflammatory plaques with peripheral nodules on the trunk and the extremities, 5 maculopapular eruption, vesiculobullous lesions, and pupura. 6 Because there is no specific serologic test for c-PAN, the diagnosis relies on clinicopathologic correlation. Biopsy reveals a necrotizing vasculitis involving medium-sized arteries in the deep dermis or subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…21,26 Cutaneous PAN has also been reported in children. 28 This was characterised by onset in the first decade of life and higher incidence of peripheral gangrene. In these 10 cases seen at PGI, Chandigarh, the authors reported possible association with diphtheria-pertussis tetanus immunisation (one), drugs (two), streptococcal infection (two), wasp sting (one) and falciparum malaria (one).…”
mentioning
confidence: 99%